Pengembangan Bahan Ajar Tema 1 (Indahnya Kebersamaan) Menggunakan Google Sites Kelas IV - M. Romadlon Habibullah; Suttrisno Suttrisno; Lia Pulviana (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2022)
This study aims to discover how to develop pedagogical material using Google sites in the 4th grade. This study also aims to determine the results of the development of teaching materials related to the validity and student responses to the developed teaching materials, as well as to determine the implementation related to the use of google sites-based teaching materials. This research is a type of development research (R&D). The method used is the development model developed by Bord & Gall. The product developed in this research is a google sites website. This study uses an instrument using a questionnaire to determine the validity, student responses, and implementation related to the use of google sites. Based on the validation of media experts, media experts obtained an average percentage of 81%, material experts 94%, linguists 89% and can be categorized as